Implementing an online learning community for a geography digital library. - Chew, Weng Leong. (2008)
This dissertation aims to implement an online learning community on GeogDL, a Web-based geography digital library. A prototype of online chat and discussion forum was developed for this project using object-oriented methodology. A small-scale evaluation was conducted to examine the usability of the system. In addition, both positive and negative feedback were also gathered.